Initial screening of poly(ethylene glycol) amino ligands for affinity purification of plasmid DNA in aqueous two-phase systems - Silva, Nuno Miguel Sampaio Ribeiro Magalhães (2021)
Gene therapy and DNA vaccination are among the most expected biotechnological and medical advances for the coming years. However, the lack of cost-effective large-scale production and purification of pharmaceutical-grade plasmid DNA (pDNA) still hampers their wide application. Downstream processing, which is mainly chromatography-based, of pDNA remains the key manufacturing step. Despite its high resolution, the scaling-up of chromatography is usually difficult and presents low capacity, resulting in low yields. Alternative methods that are based on aqueous two-phase systems (ATPSs) have been studied. Although higher yields may be obtained, its selectivity is often low. In this work, modified polymers based on poly(ethylene glycol) (PEG) derivatisation with amino groups (PEGamine) or conjugation with positively charged amino acids (PEGlysine, PEGarginine, and PEGhistidine) were studied to increase the selectivity of PEGdextran systems towards the partition of a model plasmid. A two-step strategy was employed to obtain suitable pure formulations of pDNA. In the first step, a PEGdextran system with the addition of the affinity ligand was used with the recovery of the pDNA in the PEG-rich phase. Then, the pDNA was re-extracted to an ammonium-sulphate-rich phase in the second step. After removing the salt, this method yielded a purified preparation of pDNA without RNA and protein contamination.